2009
DOI: 10.1175/2008jcli2243.1
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Atmosphere–Ocean Interactions in a Conceptual Framework

Abstract: Statistical analysis of observations (including atmospheric reanalysis and forced ocean model simulations) is used to address two questions: First, does an analogous mechanism to that of El Niñ o-Southern Oscillation (ENSO) exist in the equatorial Atlantic or Indian Ocean? Second, does the intrinsic variability in these basins matter for ENSO predictability? These questions are addressed by assessing the existence and strength of the Bjerknes and delayed negative feedbacks in each tropical basin, and by fittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
102
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 42 publications
21
102
0
Order By: Relevance
“…These findings are in agreement with the results of Dommenget et al (2006);Jansen et al (2009), who used a simple recharge oscillator model fitted to observations; and Frauen and Dommenget (2012) with their hybrid coupled model. Utilizing the BJ index formula as devised by Jin et al (2006), we further show that the underlying thermocline mode is enhanced.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in agreement with the results of Dommenget et al (2006);Jansen et al (2009), who used a simple recharge oscillator model fitted to observations; and Frauen and Dommenget (2012) with their hybrid coupled model. Utilizing the BJ index formula as devised by Jin et al (2006), we further show that the underlying thermocline mode is enhanced.…”
Section: Discussionsupporting
confidence: 90%
“…Keenlyside and Latif (2007) showed that all three elements of the Bjerknes feedback exist in the Atlantic but are weaker than in the Pacific, resulting in a 50% lower growth rate for anomalies. From a statistical analysis of observations as well as a conceptual recharge oscillator model Jansen et al (2009) also found that Bjerknes feedbacks are active in the Atlantic but more strongly damped than in the Pacific. As pointed out by Chang et al (2006), whether the feedback can sustain itself depends on the strength of the subsurface ocean response and the connection between subsurface and surface.…”
Section: Introductionmentioning
confidence: 92%
“…5 for Reynolds SST versus NCEP wind stress (1982, NEMO-ORCA05 (1958), and SODA (1958 Keenlyside and Latif (2007) and Jansen et al (2009) used wind stress anomalies in the western half of the basin to define the relationship between zonal wind stress and SST because this is where the wind stress response to eastern equatorial SST anomalies is strongest. In the BJ index definition, however, dynamical consistency requires that the wind stress response to SST forcing is computed for the region that is used to estimate the ocean response to that wind stress forcing.…”
Section: Zonal Advection Feedbackmentioning
confidence: 99%
“…The pioneering work of [4] and also [6][7][8] demonstrated that an Atlantic Niño (Niña) increases the probability for a Pacific La Niña (El Niño) event several months later. This inter-basin teleconnection is also verified in the ATL_VAR experiment.…”
Section: Atlantic Niñomentioning
confidence: 99%